Analysis of Coliform and Colifecal Total Pollution Test on Various Types of Drinking Water Using the MPN (Most Probable Number) Method - Wanda Aulya; Fadhliani Fadhliani; Vivi Mardina (Serambi Journal of Agricultural Technology, 2020)
Water is the main source for life and also the most severe substance caused by pollution. The mandatory parameters for determining microbiological quality of drinking water are total non-fecal Coliform bacteria and Coliform fecal (Escherichia coli). Coliform bacteria are a group of microorganisms commonly used as indicators, where these bacteria can be a signal to determine whether a water source has been contaminated by bacteria or not, while fecal Coliform bacteria are indicator bacteria polluting pathogenic bacteria originating from human feces and warm-blooded animals (mammals) . The water inspection method in this study uses the MPN (Most Probable Number) method which consists of 3 tests, namely, the presumption test, the affirmation test, and the reinforcement test. The results showed that of 15 drinking water samples 8 samples were tested positive for Coliform bacteria with the highest total bacterial value of sample number 1, 15 (210/100 ml), while 7 other samples were negative. From 8 positive Coliform samples only 1 sample was stated to be negative fecal Coliform bacteria and 7 other samples were positive for Coliform fecal bacteria with the highest total bacterial value of sample number 1 (210/100 ml).